2021
DOI: 10.1007/s13300-021-01078-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Dosing Conditions on the Pharmacokinetics of Oral Semaglutide, a Human Glucagon-Like Peptide-1 Analogue in a Tablet Formulation

Abstract: Introduction: Oral semaglutide is a novel tablet formulation of the human glucagon-like peptide-1 analogue semaglutide. In two trials, the effects of prior food ingestion (food effect), post-dose fasting period and water volume with dosing (dosing conditions) on oral semaglutide pharmacokinetics were investigated. Methods: Subjects received once-daily oral semaglutide for 10 days. In the food-effect trial, 78 healthy subjects were randomised 1:1:1 to fed (meal 30 min pre-dose; 240 mL water with dosing), fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 21 publications
0
48
0
1
Order By: Relevance
“…Oral semaglutide absorption increased with longer postdose fasting periods and was comparable when administered with either 50 or 120 mL of water [57]. Complete tablet erosion was observed regardless of water volume but occurred at a slower rate with 50 mL versus 240 mL, resulting in higher semaglutide plasma exposure with lower water volumes (Fig.…”
Section: Food and Dosing Conditionsmentioning
confidence: 90%
See 1 more Smart Citation
“…Oral semaglutide absorption increased with longer postdose fasting periods and was comparable when administered with either 50 or 120 mL of water [57]. Complete tablet erosion was observed regardless of water volume but occurred at a slower rate with 50 mL versus 240 mL, resulting in higher semaglutide plasma exposure with lower water volumes (Fig.…”
Section: Food and Dosing Conditionsmentioning
confidence: 90%
“…In phase I studies, food and drink were found to impact the absorption of oral semaglutide, with limited or no measurable absorption reported in fed participants [57].…”
Section: Food and Dosing Conditionsmentioning
confidence: 99%
“…After 15–35 min of oral intake, the medication reaches its maximal concentration [ 32 ]. As food interferes with drug absorption, oral semaglutide should be given while fasting [ 35 ]. Semaglutide exposure was unaffected by the amount of water used to take the drug [ 35 ].…”
Section: Pharmacodynamics and Pharmacokinetics Of Oral Semaglutidementioning
confidence: 99%
“…As food interferes with drug absorption, oral semaglutide should be given while fasting [ 35 ]. Semaglutide exposure was unaffected by the amount of water used to take the drug [ 35 ]. However, the higher the semaglutide exposure, the longer the post-dose fasting time; hence, at least 30 min of post-dose fasting is recommended [ 35 ].…”
Section: Pharmacodynamics and Pharmacokinetics Of Oral Semaglutidementioning
confidence: 99%
See 1 more Smart Citation